Legal Certainty Aspects in Regulation of the Attorney General Number 15 of 2020 Concerning Termination of Prosecution Based on Restorative Justice - Sardjana Orba Manullang; Rai Iqsandri; Mawarni Fatma; Avelia Rahmah Y. Mantali (LEGAL BRIEF, 2022)
There have been many sharp criticisms regarding law enforcement by law enforcement officials where small cases that could be resolved through peaceful efforts ended up in court. In 2020, the Attorney General issued Prosecutor Regulation Number 15 of 2020 concerning termination of prosecution. It is necessary to pay attention to the legal certainty aspect of the regulation when it is implemented. This study aims to analyze the aspect of legal certainty in the Prosecutor's Regulation Number 15 of 2020 concerning termination of prosecution based on restorative justice. Study this law uses a normative juridical approach Statutory Approach, the "statuta approach", and Conceptual Approach, the "conceptual approach". The results of the study concluded thatThe aspect of legal certainty lies in the guidelines that have been made by determining and limiting the requirements and implementation of termination of prosecution based on restorative justice. Service Regulation Number 15 of 2020 was made to support law enforcement with legal certainty, where restorative justice is given a clear, firm and comprehensive legal basis.